2016
DOI: 10.1038/ncomms12255
|View full text |Cite
|
Sign up to set email alerts
|

Structure of the tsunamigenic plate boundary and low-frequency earthquakes in the southern Ryukyu Trench

Abstract: It has been recognized that even weakly coupled subduction zones may cause large interplate earthquakes leading to destructive tsunamis. The Ryukyu Trench is one of the best fields to study this phenomenon, since various slow earthquakes and tsunamis have occurred; yet the fault structure and seismic activity there are poorly constrained. Here we present seismological evidence from marine observation for megathrust faults and low-frequency earthquakes (LFEs). On the basis of passive observation we find LFEs oc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
71
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 51 publications
(77 citation statements)
references
References 36 publications
6
71
0
Order By: Relevance
“…In contrast, clear slant reflectors can be traced to a depth of ~25 km, as shown by arrows in the MCS record, and these reflection signals have a negative polarity, indicating an abrupt decrease in velocity at the reflector. Arai et al (2016) observed similar reflection signals in the vicinity of ECr5, and they suggested the reflector is a possible tsunamigenic fault of the 1771 Meiwa Tsunami (Yaeyama Earthquake: M~8). However, there is no significant deformation at the seafloor.…”
Section: Subduction Of the Philippine Sea Platementioning
confidence: 52%
See 3 more Smart Citations
“…In contrast, clear slant reflectors can be traced to a depth of ~25 km, as shown by arrows in the MCS record, and these reflection signals have a negative polarity, indicating an abrupt decrease in velocity at the reflector. Arai et al (2016) observed similar reflection signals in the vicinity of ECr5, and they suggested the reflector is a possible tsunamigenic fault of the 1771 Meiwa Tsunami (Yaeyama Earthquake: M~8). However, there is no significant deformation at the seafloor.…”
Section: Subduction Of the Philippine Sea Platementioning
confidence: 52%
“…This indicates high pore pressure at the subduction interface in the deeper part and weak interplate coupling in the Ryukyu Trench subduction zone, as Arai et al (2016) suggested. In contrast, Goto (2013) suggested strong plate coupling caused the 1911 Kikai-jima Earthquake in the northern Ryukyu Trench.…”
Section: Subduction Of the Philippine Sea Platementioning
confidence: 64%
See 2 more Smart Citations
“…Low-frequency earthquakes (LFEs), which are categorized as seismically slow earthquakes with dominant frequencies of several Hertz, have been observed by ocean-bottom seismometers in the southern Ryukyu Trench (Arai et al 2016). For example, a swarm of LFEs was detected at the depth of 15-25 km in the southern Ryukyu Trench.…”
Section: Introductionmentioning
confidence: 99%